Dermoscopic evaluation of efficacy of 308 nm Excimer Laser in treatment of idiopathic guttate hypomelanosis - A descriptive longitudinal study: Efficacy of excimer laser in IGH - Kalegowda, Deepadarshan; Kumar B, Madegowda Shashi; Harish M, Rajegowda; C B, Meghana (Journal of Pakistan Association of Dermatologists, 2023)
Background: Idiopathic guttate hypomelanosis (IGH) is a frequent benign acquired leukodermic dermatosis characterized by numerous, discrete, hypopigmented‑to‑depigmented macules. A Variety of treatment approaches were tried for this condition with varying degree of success. The Purpose of this study is to dermoscopically evaluate the effectiveness of 308 nm Excimer laser for repigmentation of idiopathic guttate hypomelanosis. Methods: A total of 44 patients were recruited for the study. In each patient five IGH macules were treated with 308 nm Excimer laser twice weekly for 3 months. The improvement in pigmentation was graded as ≤25% ‑ minimal, 26%–50% ‑ moderate, 51%–75% ‑ good, and >75% ‑ excellent response. Results: A total of 40 patients completed the study. Out of the 200 macules treated with Excimer laser 41.5% macules showed excellent improvement, 31% macules showed a good response, 21% macules showed moderate response and 6.5% macules showed minimal response. Side effects such as post inflammatory hyperpigmentation was noticed in 9% of IGH macules. Conclusion: 308nm excimer laser is a simple, safe, outpatient procedure for effective induction of pigmentation in IGH macules with minimum adverse effects and good patient satisfaction score.